Doing business in Kakuma: Refugees, entrepreneurship, and the food market - Betts, A; Delius, A; Rodgers, C; Sterck, O; Stierna, M (Refugee Studies Centre, 2019)
This report draws upon a business survey with food retailers to assess the impact of the ‘Bamba Chakula’ model of electronic food transfers and business contracts. The Kakuma refugee camps have become popularly associated with entrepreneurship. In 2016, the Kalobeyei settlement was opened 3.5 kms away from the Kakuma camps, with the intention of promoting the self-reliance of refugees and the host population, and delivering integrated services to both. Its development is guided by the Kalobeyei Integrated Social and Economic Development Programme (KISEDP), which offers a range of innovative, market-based approaches to refugee protection that diverge from the conventional aid model implemented in Kakuma. There have been few studies that examine the emergence of refugee-led markets at the business level, whether in the Kakuma camps, in the Kalobeyei settlement, or elsewhere. In order to address this gap, our research aimed to study one particular sector: the food market. This sector is of particular interest because it is such a significant part of economic life in refugee camps, and because it is heavily shaped by the modalities of food assistance provided by the international community. Kakuma is currently undergoing a gradual transition from in-kind food assistance to cash-based assistance, and as an interim step, it has introduced a food provision model called Bamba Chakula.